PROBLEMATIKA SEKOLAH DALAM MENGIMPLEMETASIKAN KURIKULUM MERDEKA (IKM) DI MADRASAH IBTIDAIYAH NEGERI 2 KOTA BENGKULU - Asvio, Nova; Kembar, Putri (Journal of Primary Education, 2023)
The implementation of the Independent Curriculum at MIN 2 Bengkulu has been running for almost two years, from 2022 to 2024, the Implementation of the Independent and Independent Curriculum has changed. The implementation is carried out in stages. This research aims to describe and analyze school problems in implementing the Independent Curriculum. Apart from that, this research also aims to find out how schools are trying to overcome problems in implementing the independent curriculum at MIN 2 Bengkulu. This research is a type of field research with a qualitative descriptive approach. The data collection process was carried out using observation, interview and documentation techniques. Data analysis was carried out using data reduction methods, data presentation, and drawing conclusions. The results of the research show that the school's problems in IKM include: Lack of quality human resources, there is no solution yet for teachers to get SIMPKB accounts for the main administrative requirements in accessing teacher mobilization program accounts, and the implementation of P5P2RA takes up too much of the students' parents' time. The school's efforts to overcome problems in SMEs include establishing good cooperation with students' parents, providing adequate facilities and infrastructure, and increasing the effectiveness of supervisors.